Pengaruh Program Field Facilitator Bertani Untuk Negeri Terhadap Produktivitas Petani di Kelompok Tani Kaswata di Desa Lambara Kecamatan Ambulava Kabupaten Sigi Provinsi Sulawesi Tengah - Idong, Yuliantri Maharani; Rato, Yoseph Yakob Da (Peneliti.net, 2024)
Corn is the second most important food crop commodity after rice, based on the order of staple foods in the world. The use of corn as a food and feed ingredient continues to increase. Corn is one of the main food crop commodities, which has a strategic role in agricultural development and the national economy. This research was carried out at the Kaswata Farmer Group, Lambara Village, Tanambulava District, Sigi Regency., with the aim of knowing the implementation of extension activities, extension materials, farmers' adoption of agricultural extension. Field Facilitator Farming for the Country in the Kaswata Farmer Group and to determine the influence of the implementation of extension activities, extension materials, farmer adoption of agricultural extension Field Facilitator Farming for the Country on the productivity of the Kaswata Farmer Group in Lambara Village, Tanambulava District, Sigi Regency. The sample consisted of farmers in the Kaswata Farmer Group. The sample was determined by census or the entire population was sampled by interviewing farmers directly with a sample size of 30 respondents. The data analysis model used is descriptive analysis, multiple linear regression method which is first carried out using a Likert scale with scores. The results of this research show that the effect of the extension program is 90.00%. The simultaneous test or F test states that all the variables have a real effect. Based on the t test with a confidence level of 95% and a significance of 5%, the implementation of extension activities, extension materials, farmer adoption have a significant effect on the productivity of corn farmers.